Psalm 49 and the book of Qohelet - Spangenberg, I. J. I. (Verbum et ecclesia, 1997)
Psalm 49 and the Book of Qohelet. Although a number of scholars have criticised Casetti's analysis of Psalm 49. Zenger and Bossfeld employed his ideas in their recent commentary on the Psalms. According to these scholars the psalm consists of two distinct layers: a basic pessimistic psalm to which a second author later added two further strophes and an introduction. The basic psalm reflects the tone of the Book of Qohelet, but probably originated prior to that book as it does not reflect a hellenistic background. This article argues that the psalm should be read with the aid of Albertz' description of the social situation in Judaea during the fifth century BeE. There is no basis for splitting the psalm into two layers. Rather, Psalm 49 addresses two segments of the Judaean upper class.